Migration, mental health and social identity in Toni Morrison's trilogy - Motlagh, Leila Tafreshi (2016)
This interdisciplinary study attempts to bridge the gap between Migration literature and Trauma literature, by synthesizing a theoretical framework constructed from migration theories, mental health and social identity. For this purpose, it systematically addresses typology of migration and related theories as well as mental health issues, such as trauma, stress and coping strategies. Migration, which is linked to a number of social problems and health issues, is a major global concern recognized by the United Nations (UN), the Division for the Advancement of Women (DAW), the World Health Organization (WHO), and the World Mental Health (WMH). In line with the global concern, this interdisciplinary thesis seeks to analyse Toni Morrison's trilogy, Beloved (1987), Jazz (1993) and Paradise (1997), generally regarded as migration literature. The WHO defines mental health as a state of well-being whereby individuals can cope with the normal stresses of life and productively contribute to their community. WHO notes the significant rise in mental health problems and predicts that this will be the second greatest cause of death and disability, by the year 2020. According to Dinesh Bhugra, the migration process comprising pre-migration, migration and post-migration is potentially stressful and a leading cause of mental health problems. As such, the application of both adaptive (problem-focused strategy) and maladaptive (avoidance and emotion-focused strategies) coping mechanisms become critical to the maintenance of mental health. The push factor of migration theory is mainly associated with heightened trauma, as manifested in Toni Morrison's novels through the forced migratory journeys undertaken by the lead female characters. Since post-migration stresses, such as resettlement, unemployment and social identity can exceed people’s coping resources. A systematic textual analysis of Toni Morrison's migration literature reveals that mental health problems in migrant women are partly due to gender-specific stresses, premigration traumas, post-migration stress factors and post-traumatic stress disorder (PTSD). More importantly, maladaptive coping strategies and lack of social support can undermine mental health. Consequently, the critical psychological states of migrant women in Toni Morrison's trilogy, result from a combination of migration stresses, traumatic events, maladaptive coping strategies and lack of social support.